2003
DOI: 10.1016/s0009-9236(03)00199-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of high doses of intramuscular and oral heroin in narcotic addicts

Abstract: On the basis of the linear pharmacokinetics, the high bioavailability of intramuscular diacetylmorphine, and the rapid and extended morphine absorption from oral diacetylmorphine, the intramuscular and oral routes can be recommended as safe and feasible alternatives to the intravenous route for medical prescription of diacetylmorphine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 14 publications
3
43
0
Order By: Relevance
“…Because IgG has two binding sites per antibody molecule, 1-10 mM drug-binding sites were available. This is within a clinical relevant concentration range as C max of 6-MAM has been measured to be 5.0-17.5 mM after intravenous injection of heroin in heroin users (Rentsch et al, 2001;Girardin et al, 2003;Rook et al, 2006b). One of the advantages of passive immunization is the possibility to easily increase the antibody levels in the blood by giving higher doses of antidrug mAb.…”
Section: Controlmentioning
confidence: 64%
“…Because IgG has two binding sites per antibody molecule, 1-10 mM drug-binding sites were available. This is within a clinical relevant concentration range as C max of 6-MAM has been measured to be 5.0-17.5 mM after intravenous injection of heroin in heroin users (Rentsch et al, 2001;Girardin et al, 2003;Rook et al, 2006b). One of the advantages of passive immunization is the possibility to easily increase the antibody levels in the blood by giving higher doses of antidrug mAb.…”
Section: Controlmentioning
confidence: 64%
“…These preclinical data contrast with several human studies that found heroin to be the predominant opioid in plasma shortly (2 to 10 minutes) after similar i.v. doses of heroin (Comer et al, 1999;Girardin et al, 2003). The metabolism of heroin to 6-MAM and morphine in plasma is attributable to esterases in blood as well as non-enzymatic degradation (Salmon et al, 1999;Selley et al, 2001;Rook et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, many patients must receive prescribed diacetylmorphine orally rather than intravenously due to venosclerosis [10]. We therefore studied the kinetics of diacetylmorphine and its metabolites such as morphine after oral diacetylmorphine in opioid-dependent patients [11] and found that oral diacetylmorphine, up to doses of 600 mg, led to only negligible systemic diacetylmorphine and monoacetylmorphine concentrations. However, our study in opioid-dependent patients showed for the first time that high doses of oral diacetylmorphine, considered as a morphine prodrug, lead to unexpectedly high morphine bioavailabilities of 64, 66 and 72% for average doses of 206, 413 and 619 mg, respectively.…”
Section: Introductionmentioning
confidence: 99%